ANALISIS PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP CUSTOMER LOYALTY MELALUI CUSTOMER SATISFACTION DAN CUSTOMER VALUE TERHADAP CUSTOMER LOYALTY (Studi Pada Stove Syndicate Semarang) - Maulitasari Raharjo, Keisha; Santosa, Suryono Budi (Faculty of Economics and Business Diponegoro University, 2015)
This study aims to explain the impact of service quality and product quality to customer loyalty through customer satisfaction and customer value to customer loyalty at Stove Syndicate Semarang. This study uses a type of sampling in the form of non-probability sampling due to the complete population data is unknown, while the sampling method used in this research is purposive sampling , the sampling technique with particular consideration. The collection of data obtained from 150 customers Stove Syndicate Semarang by questionnaire consisting of closed questions with Likert scale 5. Data analysis techniques and interpretation are used to analyze the data according to the model developed in this study is a SEM (Structural Equation Modeling), which operated via AMOS ver 21.0. The results showed that customer satisfaction may mediate the relationship between quality of service and quality of product to customer loyalty shown by the positive and significant influence between variables in this study , as well as customer value on customer loyalty which also showed a positive influence and significant.